2016
DOI: 10.1371/journal.pbio.1002412
|View full text |Cite
|
Sign up to set email alerts
|

Separable Roles for a Caenorhabditis elegans RMI1 Homolog in Promoting and Antagonizing Meiotic Crossovers Ensure Faithful Chromosome Inheritance

Abstract: During the first meiotic division, crossovers (COs) between homologous chromosomes ensure their correct segregation. COs are produced by homologous recombination (HR)-mediated repair of programmed DNA double strand breaks (DSBs). As more DSBs are induced than COs, mechanisms are required to establish a regulated number of COs and to repair remaining intermediates as non-crossovers (NCOs). We show that the Caenorhabditis elegans RMI1 homolog-1 (RMH-1) functions during meiosis to promote both CO and NCO HR at ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(87 citation statements)
references
References 80 publications
(90 reference statements)
9
77
1
Order By: Relevance
“…Unexpectedly, these studies revealed that Rmi1 and Top3 act independently of Sgs1 to disentangle chromosomes in late meiotic prophase, allowing for proper chromosomal segregation [12,40]. Similar BLM-independent roles for RMI1 and TOP3α have been described in Arabidopsis [20, 4143] and C. elegans [44], but it is likely that functions described below for BLM orthologs also require these interacting proteins.…”
Section: S Cerevisiae Sgs1: the Pioneering Meiotic Pathway Regulatormentioning
confidence: 86%
“…Unexpectedly, these studies revealed that Rmi1 and Top3 act independently of Sgs1 to disentangle chromosomes in late meiotic prophase, allowing for proper chromosomal segregation [12,40]. Similar BLM-independent roles for RMI1 and TOP3α have been described in Arabidopsis [20, 4143] and C. elegans [44], but it is likely that functions described below for BLM orthologs also require these interacting proteins.…”
Section: S Cerevisiae Sgs1: the Pioneering Meiotic Pathway Regulatormentioning
confidence: 86%
“…The localization of Zip3 orthologs is consistent with their involvement in the transformation of early recombination intermediates into crossovers (Box1). All members of the family exhibit a broad pattern of colocalization with the SC early in prophase, followed by a restriction to a smaller subset of foci which overlap with cytological CO markers (MutSg, MutLg, or recombination nodules, SC structures which correlate with crossing over [30]) [16,18,20,22,24,28,[31][32][33][34]. Consequently, the collective analyses indicate that SUMO and/or ubiquitin E3 ligase-like proteins localize to the SC and to CO sites to mediate the formation of crossovers.…”
Section: Conserved Roles For the Zip3 Family During Meiotic Prophasementioning
confidence: 94%
“…All members of the family exhibit a broad pattern of colocalization with the SC early in prophase, followed by a restriction to a smaller subset of foci which overlap with cytological CO markers (MutSg, MutLg, or recombination nodules, SC structures which correlate with crossing over [30]) [16,18,20,22,24,28,[31][32][33][34]. All members of the family exhibit a broad pattern of colocalization with the SC early in prophase, followed by a restriction to a smaller subset of foci which overlap with cytological CO markers (MutSg, MutLg, or recombination nodules, SC structures which correlate with crossing over [30]) [16,18,20,22,24,28,[31][32][33][34].…”
Section: Conserved Roles For the Zip3 Family During Meiotic Prophasementioning
confidence: 99%
See 1 more Smart Citation
“…Alteration in crossover distribution in the brc-1 mutant may result from changes in the chromatin landscape, which has been linked to BRCA1 function in mammals (BROERING et al 2014;DENSHAM et al 2016), and has been shown to alter crossover patterning (MEZARD et al 2015;YU et al 2016). A surprising number of C. elegans meiotic mutants display altered crossover distribution (ZETKA AND ROSE 1995;MENEELY et al 2012;SAITO et al 2012;SAITO et al 2013;WAGNER et al 2010;CHUNG et al 2015;HONG et al 2016;JAGUT et al 2016;Janisiw et al 2020). While the underlying mechanisms are not clear, it may be a consequence of altering the use of crossover versus non-crossover pathways within a particular chromatin environment as suggested by Saito and Colaiacovo (SAITO AND COLAIACOVO 2017).…”
Section: Brc-1-brd-1 Function When Male Meiosis Is Perturbedmentioning
confidence: 99%